Advances in ICP-MS-Based Nanoparticle Characterization: Techniques and Challenges in Biological Sample Analysis - Gregar, Filip; Baron, Daniel; Pluháček, Tomáš (Journal of separation science, 2025)
The increasing use of engineered nanoparticles (NPs) in consumer and biomedical products has raised concern over their potential accumulation, transformation, and toxicity in biological systems. Accurate analytical methods are essential to detect, characterize, and quantify NPs in complex biological matrices. Inductively coupled plasma mass spectrometry (ICP-MS) has emerged as a leading technique due to its high sensitivity, elemental selectivity, and quantitative capabilities. This review critically evaluates recent advances (from January 2020 onward) in ICP-MS-based methods for analysis of NPs in biological samples. Two main strategies are discussed: single-particle ICP-MS (spICP-MS) and hyphenated techniques coupled to ICP-MS. spICP-MS allows direct determination of particle size, concentration, and metal content at environmentally relevant levels. It is the most widely used approach and is therefore examined in greater detail, with attention to extraction procedures, particle types, sample matrices, and inherent limitations. Advances in laser ablation spICP-MS for tissue imaging and spatially resolved NPs detection are also covered. Methods using hyphenated techniques, such as hydrodynamic chromatography, size-exclusion chromatography, capillary electrophoresis, Taylor dispersion analysis, and field-flow fractionation, are increasingly employed to address limitations spICP-MS. These approaches can provide enhanced insight into particle size distributions, aggregation behavior, and interactions with complex sample matrices. This review offers a comparative evaluation of both single-particle and hyphenated methods, discussing their respective advantages and limitations. Emphasis is placed on the complementarity of these techniques and how their combined use can offer a more complete understanding of NPs' fate in biological systems.
Keywords: Nanoparticles; biological samples | inductively coupled plasma mass spectrometry (ICP‐MS) | nanoparticles | separation | single particle; nanočástice; hmotnostní spektrometrie; Animals; lidé; Particle Size; Mass Spectrometry; Humans; zvířata; velikost částic